Breach of Contract in the View of Islamic law: A Case Study on the Partnership Agreements of Mini BRI-link - Wamafma, Filep; Martha Sasea, Enni (DIKTUM: Jurnal Syariah dan Hukum, 2023)
As a banking industry, BRI has several financial services and products whose role is to satisfy the community's needs. Services and products provided by BRI include EDC Merchant machines, ATMs, E-Bangking, sales of third party products, such as Telkom products, PLN, credit cards and EDC mini BRI ATMs or BRILink Mobile. It is undeniable that sometimes there are some problems in the field such as defaults. Default is a form of negligence committed by one party that results in losses to the other party. This will be reviewed from Islamic Law using qualitative research methods with the research location located in Manokwari Regency, namely at the Manokwari Branch of the BRI Bank office (BRILink Section). In Indonesia itself, DSN-MUI Fatwa No. 17/DSN-MUI/IX/2000 states that fines for consumers who are competent but unwilling to pay their debts are contained in the category of ta'zir that is allowed. As long as the status of the property is in the Yad Trust, the debtor is not obliged to compensate it for foreign causes